Detection of Methylobacterium species by 16S rRNA gene-targeted PCR. - Nishio, T (1997)
We designed PCR primers for specific amplification of the 16S rRNA genes of seven species of the genus Methylobacterium. All of the pairwise species tested were successfully differentiated by PCR detection with a combination of five primer sets, with the exception of M. extorquens and M. rhodesianum. These primers did not cross-react with closely related bacteria in the alpha subclass tested.